Can maxilla and mandible bone quality explain differences in orthodontic mini-implant failures? - Omar Melendres Ugarte; Ivan Onone Gialain; Naor Maldonado de Carvalho; Gisele Lie Fukuoka; Rafael Yague Ballester; Paolo Maria Cattaneo; Marina Guimarães Roscoe; Josete Barbosa Cruz Meira (Biomaterial Investigations in Dentistry, 2021)
Purpose: This study aimed to compare the risk of orthodontic mini-implant (OMI) failure between maxilla and mandible. A critical analysis of finite-element studies was used to explain the contradiction of the greatest clinical success for OMIs placed in the maxilla, despite the higher quality bone of mandible. Materials and Methods: Four tridimensional FE models were built, simulating an OMI inserted in a low-dense maxilla, control maxilla, control mandible, and high-dense mandible. A horizontal force was applied to simulate an anterior retraction of 2 N (clinical scenario) and 10 N (overloading condition). The intra-bone OMI displacement and the major principal bone strains were used to evaluate the risk of failure due to insufficient primary stability or peri-implant bone resorption. Results: The OMI displacement was far below the 50–100 µm threshold, suggesting that the primary stability would be sufficient in all models. However, the maxilla was more prone to lose its stability due to overload conditions, especially in the low-dense condition, in which major principal bone strains surpassed the pathologic bone resorption threshold of 3000 µstrain. Conclusions: The differences in orthodontic mini-implant failures cannot be explained by maxilla and mandible bone quality in finite-element analysis that does not incorporate the residual stress due to OMI insertion.